Quality of Construction Works of Sub-district Administrative Organization in Chonburi Province - เงินมีศรี, สุธรรม; สำราญวานิช, ทวีชัย; วงษ์แก้ว, อานนท์; ใจยงค์, อมรชัย (Frontiers in Engineering Innovation Research, 2015)
This paper aims to determine the quality of construction managements of sub-district administrative organizations (SAOs) in Chonburi province. Evaluation of construction managements for those SAOs was done by surveying of the authorities who are responsible in construction managements of SAOs as Chief Executive of the SAOs, Chief Administrator of the SAOs, and/or Chief Construction division of the SAOs. The forty-eight questionnaires were distributed to each SAO, completed and returned by those authorities. By applying the maturity model concept, the maturity level evaluation system (MLES) level of construction managements was categorized into five levels ranging from 1 to 5. As the results from statistical analysis, it was found that 6.25 percent of those forty-eight sub-district Administrative Organizations had MLES below the first level. It was found that 4.17 percent of SAOs practiced with MLES level 1, and 31.25 percent was in MLES level 2. Among those SAOs, 6.25 percent showed the MLES in construction managements at levels of 3 and 4. There was 45.83 percent of SAOs in Chonburi province performed at the MLES level 5. The study also extended to evaluate the problems particularly related to the construction managements in SAOs. The results showed that the problem related to survey for construction designs had a level of medium. The problems created from design and estimation of construction work, construction control work, quality inspection work and maintenance and contract coverage work show level of high. Moreover, it was found that the SAOs in Chonburi province have the strength on the study of laws and rules before starting the project and have the weakness on the lack of persons in construction management.